Оцінка впливу виробничих витрат на собівартість продукції - Колісник, Олена Пилипівна; Суходольська, Дарина Вікторівна (Видавничий дім «Гельветика», 2023)
Стаття присвячена оцінці впливу виробничих витрат на собівартість продукції. Визначено, що витрати на виробництво є важливим стратегічним фактором, який безпосередньо впливає на собівартість продукції, а, отже, на прибутковість підприємства. Виділено та розглянуто витрати на виробництво за способом включення до собівартості, ступенем реагування на зміну обсягів діяльності та можливістю планування діяльності. Визначено, що взаємозв'язок між різними видами витрат та їхнім впливом на собівартість є складним і взаємопов'язаним. Розглянуто ключові фактори, що впливають на собівартість продукції та фактори, що впливають на зміни витрат на виробництво. Конкретні фактори можуть варіюватися залежно від галузі, виду продукції та контексту підприємства. Завдяки ретельному аналізу та контролю витрат на різних етапах виробництва, підприємства можуть знизити собівартість продукції, поліпшити конкурентоспроможність та досягти позитивних фінансових результатів.

The purpose of this article is to assess the impact of production costs on the cost of production in the current economic environment characterized by fierce competition. The relevance of the topic lies in the need to understand the impact of production costs on production costs, since modern market conditions require a constant search for ways to reduce production costs so that the enterprise can remain competitive in the market and meet the needs of consumers. To achieve this goal, the article uses the methods of analysis and synthesis, comparison and abstraction. The article determines that production costs affect the cost of production both directly and indirectly. The direct impact is manifested in the fact that production costs are directly included in the cost of production. The indirect effect is manifested in the fact that production costs affect the level of labor productivity, production structure and other factors that also affect the cost of production. The production costs are allocated and considered by the method of inclusion in the cost of production, the degree of response to changes in the volume of activities and the possibility of planning activities. It is determined that the relationship between different types of costs and their impact on production costs is complex and interrelated. The practical value of the article lies in the fact that the analysis of the impact of production costs on the cost of production allows enterprises to identify reserves for cost reduction and develop measures for their implementation. It is also possible to implement the findings into the practice of production process management to achieve more efficient economic activity of enterprises. The results of the study can be used to make informed decisions on cost management, reduce production costs and increase the competitiveness of the enterprise. Thus, the impact of production costs on the cost of production is now more significant than before. This is due to factors such as increased competition, rising prices for raw materials and supplies, and changing consumer demands. To effectively manage costs, companies need to regularly analyze the impact of costs on production costs.
Keywords: виробничі витрати; собівартість продукції; аналіз витрат; ефективність виробництва; управління витратами; конкурентоспроможність; production costs; cost of production; cost analysis; production efficiency; cost management; competitiveness